El abordaje mediático de la mendicidad en los medios digitales Cotopaxi noticias y la hora Cotopaxi - Chacha Velasque, Luis Abelardo (2016)
This project studied the treatment of information that perform digital media Cotopaxi and Cotopaxi Time on the issue of begging. It held a record of the information that the two media published during 2010-2016. This activity was analyzed as the information they may or may not affect the reading public, especially if it comes to reporting using new technologies, in this case, through the internet. In the theoretical foundation, it begging described in Latin America, Ecuador and Cotopaxi. Begging was analyzed in terms of not being or a media entity. Also the importance of people who beg, who, despite being vulnerable group are sources of information. It discussed the reasons that make begging a valuable information object, passing it through various journalistic genres, but only with a basic content such as statistics, campaigns, events, donations and collections. The draft new interpretations of the social problem of begging, thus it was possible to raise other causes of begging in Cotopaxi as given. It is concluded that the implementation of new information should require perseverance and creativity on the part of the journalist, and do everything possible to establish a professional and especially human relationship to sources, within the framework of ethics and morality that governs journalism.